2020
DOI: 10.35848/1347-4065/ab85da
|View full text |Cite
|
Sign up to set email alerts
|

Study of loss mechanisms in temperature compensated surface acoustic wave devices based on finite element method analysis using hierarchical cascading technique

Abstract: This paper discusses loss mechanisms of temperature compensated surface acoustic wave (TC-SAW) devices using the SiO2 overcoated 128°YX-LiNbO3 (128-LN) substrate. Analysis is based on the finite element method (FEM) combined with the hierarchical cascading technique and the general purpose graphics processing unit. Three kinds of FEM model, i.e. 2.5D, three dimensional (3D) periodic and full 3D are analyzed without taking additional losses, i.e. material viscous loss, dielectric loss and electrode ohmic loss, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…8) Furthermore, R-SAWs and LSAWs have been extensively studied. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Our research group reported that a large K 2 and a small TCF can be simultaneously obtained in LT/quartz and LN/quartz structures. 19) Note that some research groups have also investigated a bonded structure comprising an LT thin plate and quartz, and obtained an LSAW resonator with high impedance ratio and large Q factor.…”
Section: Introductionmentioning
confidence: 95%
“…8) Furthermore, R-SAWs and LSAWs have been extensively studied. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Our research group reported that a large K 2 and a small TCF can be simultaneously obtained in LT/quartz and LN/quartz structures. 19) Note that some research groups have also investigated a bonded structure comprising an LT thin plate and quartz, and obtained an LSAW resonator with high impedance ratio and large Q factor.…”
Section: Introductionmentioning
confidence: 95%
“…Figure 13 shows calculated admittance of one-port SAW resonator using a SiO 2 /128 • YX-LiNbO 3 structure [49]. Three results are shown.…”
Section: Advanced Fem Simulationmentioning
confidence: 99%
“…With the increasing communication requirements, the standard surface acoustic wave (SAW) filter has a high temperature drift frequency, which produces nonlinear frequency changes to temperature changes, which seriously affects the filter performance and cannot meet certain strict requirements [ 28 ]. specifications, so BAW filters including thin-film bulk acoustic resonators and solid-mounted resonator filters have been developed to meet this requirement.…”
Section: Saw Filter Technologymentioning
confidence: 99%